BENEFITS OF INSTAGRAM AS A PROMOTIONAL MEDIUM FOR SCARLETT WHITENING PRODUCTS - Muhammad Zidane Adri Priatna Priatna; Prina Puspa Sarinining Diah; Alifa Achmadi (STIA Bagasasi, 2022)
Technological developments make progress on the ease of communication, one of which is Instagram. Instagram has become a popular alternative media in marketing products, especially among generation Z. One of them is Scarlett Whitening products. Scarlett Whitening is a local product engaged in cosmetics and skin care. This study aims to analyze the strength of EWOM of Scarlett Whitening products carried out through Instagram social media. This research uses a qualitative research method with an interpretative descriptive research type that uses in-depth interview techniques as a data collection method. The results illustrate that Instagram EWOM in terms of the three dimensions described by Goyette, et.al is appropriate up to the content stage and plays a major role in convincing generation Z to make purchasing decisions on Scarlett Whitening products through Instagram social media.